What do patients consulting in a free sexual health center know about HIV transmission and post-exposure prophylaxis? - Christelle Duteil; Elise de La Rochebrochard; Prescillia Piron; Christophe Segouin; Pénélope Troude (BMC, 2021)
Abstract Background Screening, condom use and post-exposure prophylaxis (PEP) are among existing HIV prevention strategies. However, efficient use of these strategies requires that patients have an adequate knowledge of HIV transmission routes and awareness of risk behaviors. This study aimed to assess knowledge about HIV transmission among patients who attended a free HIV and sexually transmitted infection (STI) screening center in Paris, France, and to explore the patient profiles associated with HIV-related knowledge. Methods This observational cross-sectional study included 2002 patients who attended for STI testing from August 2017 through August 2018 and completed a self-administered electronic questionnaire. Based on incorrect answers regarding HIV transmission, two outcomes were assessed: lack of knowledge and false beliefs. Factors associated with these two outcomes were explored using univariate and multivariate logistic regressions. Results Only 3.6% of patients did not know about HIV transmission through unprotected sexual intercourse and/or by sharing needles. More than one third of patients (36.4%) had at least one false belief, believing that HIV could be transmitted by sharing a drink (9.7%), kissing (17.6%) or using public toilets (27.5%). A low educational level and no previous HIV testing were associated in multivariate analyses with both lack of knowledge and false beliefs. Age and sexual orientation were also associated with false beliefs. Furthermore, 55.6% of patients did not know that post-exposure prophylaxis consists of taking emergency treatment as soon as possible after risky intercourse. Conclusions Although the main HIV transmission routes are well known, false beliefs persist and knowledge regarding PEP needs to be improved. Prevention campaigns must focus on these themes which appear as a complementary strategy to pre-exposure prophylaxis to reduce HIV infection.